Pelaksanaan Program Liga Tahfiz Dalam Meningkatkan Kualitas Hafalan Al-Qur’an - Abd Rahman; Nanda Fitriani (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2023)
The purpose of this study was to determine the implementation of the tahfiz league program in Improving the Quality of Memorization of the Qur'an at the Jabal Rahmah Mulia Education Foundation Medan which includes, implementation, evaluation to supporting and inhibiting factors. This study uses a qualitative method. Data collection was carried out by observation, interview and documentation techniques. Data analysis with the stages of data selection, data presentation, and data verification. Test the validity of the data by researchers using data triangulation, methods and time as well as extending the participation of researchers. The results of this study concluded that the implementation of the tahfiz league program was well planned and organized with technical evidence from the results of the study namely 1) Implementation was carried out according to schedule and structured 2) Evaluation was carried out routinely and in stages, namely a daily, weekly, monthly and annual assessment system 3) Supporting and inhibiting factors.